Intra-Arrest Therapeutic Hypothermia and Neurologic Outcome in Patients Admitted after Out-of-Hospital Cardiac Arrest: A Post Hoc Analysis of the Princess Trial - Macchini, Elisabetta; Dillenbeck, Emelie; Jonsson, Martin; Annoni, Filippo; Forsberg, Sune; Hollenberg, Jacob; Truhlar, Anatolij; Svensson, Leif; Nordberg, Per; Taccone, Fabio Silvio (Brain sciences, 2022)
Background: Despite promising results, the role of intra-arrest hypothermia in out-of-hospital cardiac arrest (OHCA) remains controversial. The aim of this study was to assess the effects of trans-nasal evaporative cooling (TNEC) during resuscitation on neurological recovery in OHCA patients admitted alive to the hospital. Methods: A post hoc analysis of the PRINCESS trial, including only patients admitted alive to the hospital, either assigned to TNEC or standard of care during resuscitation. The primary endpoint was favorable neurological outcome (FO) defined as a Cerebral Performance Category (CPC) of 1-2 at 90 days. The secondary outcomes were overall survival at 90 days and CPC 1 at 90 days. Subgroup analyses were performed according to the initial cardiac rhythm. Results: A total of 149 patients in the TNEC and 142 in the control group were included. The number of patients with CPC 1-2 at 90 days was 56/149 (37.6%) in the intervention group and 45/142 (31.7%) in the control group (p = 0.29). Survival and CPC 1 at 90 days was observed in 60/149 patients (40.3%) vs. 52/142 (36.6%; p = 0.09) and 50/149 (33.6%) vs. 35/142 (24.6%; p = 0.11) in the two groups. In the subgroup of patients with an initial shockable rhythm, the number of patients with CPC 1 at 90 days was 45/83 (54.2%) in the intervention group and 27/78 (34.6%) in the control group (p = 0.01). Conclusions: In this post hoc analysis of admitted OHCA patients, no statistically significant benefits of TNEC on neurological outcome at 90 days was found. In patients with initial shockable rhythm, TNEC was associated with increased full neurological recovery.
Keywords: trans-nasal evaporative cooling; cardiac arrest; intra-arrest hypothermia; outcome